Socialize the Biopore Modification and Utilization as a Composting Media and Disaster Mitigation Efforts in Blawi Village, Karangbinangun, Lamongan - Marsha Savira Agatha Putri; Nur Lathifah Syakbanah; Nur Azizah Affandy; Salwa Nabilah; Adisti Risma Putri Azzahra Arismaya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Blawi is a village where geographically located near the Bengawan Solo River crosses Lamongan Regency. During the wet season, Blawi Village often experiences flooding, however the contrary during the dry season it often experiences drought. Thus, with the background of these problems, it is necessary to carry out outreach the “Socialization and Utilization of Biopori with modification of Giving Effective Microorganism 4 (EM4)" to overcome the society problems in Blawi. This activity was held on Saturday, July 23, 2022 at 18.00 WIB until it is finished at the Blawi Village Hall, Karangbinangun District, Lamongan Regency. The event started with the opening, counseling, focus group discussion and question and answer sessions, until the closing. The participants of this activity were Blawi residents along with Karangtaruna and women society called PKK who enthusiastically participated in this activity. The counseling activity went smoothly and was well implemented, and it is hoped that similar activities can be carried out in the future so that collaboration between the academic community of the Faculty of Health Sciences, Universitas Islam Lamongan and the Blawi Village Government.